Editorial (KEMANUSIAAN The Asian Journal of Humanities, 2015)
The second issue of Volume 22 features five articles on topics in literature, heritage and philosophy. The first article is an elegant discussion of how historical fiction offers opportunities for re-reading and examining national history and literary spatiality. It achieves this by examining the literary spaces in a 1985 novel, Daerah Zeni, by the Malaysian National Laureate A. Samad Said.